Misunderstanding in the Interpretation of the Poem "Cinta Kepayang" in Gandrung by A. Mustofa Bisri - Abdul Wachid Bambang Suharto (BAHASTRA, 2021)
This research aimed to reveal misunderstanding in the interpretation of the poem â€œCinta Kepayangâ€ in the poetry book Gandrung by A. Mustofa Bisri. The characteristic of A. Mustofa Bisri poems in Gandrung is that his poems are very rich in symbols related to the thought of Islamic mysticism (Sufism). The mind is a blend of mystical experience and aesthetic experience. This study uses a qualitative approach to interpretate the poem â€œCinta Kepayangâ€. It is library research by collecting primary and secondary data related to Gandrung by A. Mustofa Bisri. The results revealed that the interpretation of â€œLoveâ€ (Cinta) was represented in two styles; first, positioning the symbolic image of women as the presence of divine beauty, second, positioning the symbolic image of women as the most perfect expression of divine love fusion.